Spasms and not Myoclonus in Subacute Sclerosing Panencephalitis. A Case Report and Review of the Literature - Gyseghem, P. Van; Andrei, A.; Presiozi, M.; Goffinon, E.; Aeby, A.; Hecke, A. Van (Neuropediatrics, 2025)
Subacute sclerosing panencephalitis (SSPE) is a neurodegenerative disease caused by the measles virus. An affected child typically presents with cognitive decline and abnormal movements, described as myoclonia. Early diagnosis is crucial for prognosis, but can be challenging because early symptoms may be subtle, and EEG findings are not always typical. We propose that better description and documentation of motor symptoms may facilitate earlier recognition of SSPE.A 4-year-old boy presented with cognitive decline and motor symptoms evolving over 6 months. The patient had a history of measles at 2 months of age. Initial investigations, conducted when he developed clinical regression and abnormal movements, were inconclusive. After a partial recovery, he relapsed with further regression, worsening of abnormal movements, and seizures. At our hospital, we diagnosed SSPE based on Dyken's criteria. EEG and EMG recordings showed movements beginning after a diffuse slow wave, followed by a flattening of the EEG line, with a typical diamond pattern on the EMG lasting 0.5 to 1 second. Movements were classified as epileptic spasms.We propose that patients with SSPE may present epileptic spasms as the abnormal motor phenomena, and not only myoclonus. Raising awareness about epileptic spasms as a clinical manifestation may aid early diagnosis of SSPE.
Keywords: subacute sclerosing panencephalitis; myoclonus; electroclinical presentation; epileptic spasms